Desenvolvimento de um programa de intervenção com famílias que cometeram violência contra crianças e adolescentes - Guimarães, Débora Ananias (2021)
Studies show that children and adolescents remain among the main victims of domestic violence, which represents failures in preventing and combating violence in the intrafamily context. The expectation of the international scientific community is that this worsens during and after the COVID-19 pandemic period, in view of that spaces considered protective (such as schools) were closed and victims they stay longer with their aggressors as a result of social isolation. It is therefore even more urgent to intensify efforts in the initiatives aimed at protecting these segments. Psychosocial intervention programs aimed at families can collaborate in the fight against violence against children and teenagers, as well as break with aggression and, eventually, minimize the recurrence of cases. However, programs of this nature are scarce and many of them, were not subjected to rigorous processes of scientific evaluation and validation, especially in the Brazilian reality. Based on these findings, the objective of this dissertation was to develop a psychosocial intervention program aimed at families who practiced intra-family violence against children and adolescents. Complementarily, the objective was to evaluate the content of the program, through analysis by expert judges on the subject. Based on the theoretical assumptions of the Cultural-Historical Psychology (PHC), the program took into account the reality of Brazilian families and the social and psychological demands of people assisted in the medium-complexity services of the Unified Social Assistance System. In this way, the program will train professionals (psychologists, social workers and educators) who work at SUAS to intervene with families The dissertation presents a chapter theory on the origin and perpetuation of intrafamily violence from the perspective of PHC. Next, the program is presented in its entirety, including the objectives of each session and the development of each activity. The subsequent chapter refers to the study validity of content conducted from the analysis of 3 expert judges on the subject of intrafamily violence and in psychosocial intervention programs. The evaluation encompassed dimensions about the structure of the intervention, contents, objectives, resources employees, among others. The main results of this study pointed to the need to review the proposed time for the execution of some activities, a adequacy of the language and contents addressed to the reality of the target audience, in addition to a qualification in materials and graphic resources. However, the study also revealed the quality, relevance and potential of the elaborated material, as well as its importance for the instrumentalization of professionals who work in the politics of social assistance. The entire investigative course, which culminated in the positive evaluation of the experts, motivated the continuation of the process of scientific validation of the intervention, which will be subjected to feasibility and effectiveness studies in the future. it is expected that the program developed in this dissertation can be widely disseminated in the contexto two national level and collaborate in strengthening families, so that they are minimized or broken cycles of violence that are perpetuated against children and adolescentes.